2018
DOI: 10.1007/s00431-018-3291-y
|View full text |Cite
|
Sign up to set email alerts
|

The association between psychological and social factors and spinal pain in adolescents

Abstract: Spinal Pain, back pain and/or neck pain, begins early in life and is strongly associated with spinal pain in adulthood. Understanding the relationship between psychological and social factors and adolescent spinal pain may be important in both the prevention and treatment of spinal pain in this age group. We aimed to determine if psychological and social factors were associated with spinal pain in a cross-sectional study of a school-based cohort of 1,279 Danish adolescents aged 11-13, who were categorized into… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 31 publications
2
24
0
1
Order By: Relevance
“…It was also higher than previously Brazilian studies carried out in a South State of Brazil, that showed a prevalence of 26.2% in the city of Rio Grande [17], 36,9% in the city of Pelotas [14]. On the other hand, the prevalence was similar to that reported in Canada [18] of 59.0%. These prevalence variations may be a result of sociocultural, demographic, economic and occupational differences of the investigated regions.…”
Section: Discussionsupporting
confidence: 56%
“…It was also higher than previously Brazilian studies carried out in a South State of Brazil, that showed a prevalence of 26.2% in the city of Rio Grande [17], 36,9% in the city of Pelotas [14]. On the other hand, the prevalence was similar to that reported in Canada [18] of 59.0%. These prevalence variations may be a result of sociocultural, demographic, economic and occupational differences of the investigated regions.…”
Section: Discussionsupporting
confidence: 56%
“…Therefore, for example, near work such as screen watching will induce more symptoms in children who need glasses compared to children with normal vision 10,[20][21][22][23][24][25][26][27][28] . Headaches and musculoskeletal symptoms in children have been shown to be associated with psychosocial stress and socioeconomic aspects 31,39 . However, these issues were not investigated in our study, and therefore the prevalence and possible effects on symptoms remain unknown.…”
Section: Discussionmentioning
confidence: 99%
“…"In addition, children in more disadvantaged families were more likely to experience spinal pain" (p. 704; see also Ballenberger et al, 2018). Batley et al (2019) were recently able to show that other social factors such as increased loneliness and lower acceptance by other students as well as psychological factors such as increased nervousness, more frequent low/bad mood, and difficulty sleeping are associated with spinal pain in adolescents (average age M = 12.6 years, SD = 0.61). These findings raise the question of the possible role of psychological and social factors in the genesis of PRP (see Ballenberger et al, 2018).…”
Section: Discussionmentioning
confidence: 99%